Analisis Implementasi Sop Prosedur Pemulangan Orang Terlantar ke Daerah Asal oleh Dinas Sosial Pemberdayaan Perempuan dan Perlindungan Anak Provinsi Bali - Zahara, Andini Salma; Prabawati, Ni Putu Anik (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The study analyzes the implementation of the Standard Operating Procedure (SOP) for the repatriation of homeless individuals to their regions of origin by the Social Service for Women’s Empowerment and Child Protection of Bali Province. Bali, as a major tourist destination, faces complex social challenges with the presence of homeless people, many of whom come from outside the region. The research employs a qualitative descriptive case study approach, utilizing in-depth interviews, participatory observation, and documentation to explore the stages, effectiveness, and obstacles of the repatriation process. The analysis is based on George C. Edwards III’s policy implementation theory, focusing on communication, resources, disposition, and bureaucratic structure. Findings indicate that the relay mechanism—where repatriation is conducted in stages through inter-regional coordination—proves efficient but faces challenges such as limited resources, administrative complexity, and the need for strong cross-sectoral cooperation. The SOP, updated annually, ensures legal and procedural clarity, but recurring cases and the reintegration capacity of the origin regions remain significant issues. The study underscores the importance of effective communication, adequate resources, and responsive service in ensuring the protection and social rights of vulnerable groups in Bali.